Continuing education of English teachers in Brazil: challenges and perspectives for teaching practice - SANTOS, Adriele Ferreira dos (2024)
Continuing education for English teachers in Brazil is crucial for the ongoing improvement of teaching practices, especially in the face of rapid pedagogical and technological changes. This research aimed to analyze the challenges and perspectives of continuing education for English teachers between 2014 and 2024. The methodology employed was a systematic literature review, utilizing data from published articles available on Google Scholar. The findings indicated that the challenges include resistance to change and a lack of adequate resources for training. Among the perspectives, the effectiveness of online training programs and collaborative practices was highlighted. The analysis revealed that, despite promising initiatives, there is a need to improve the adaptation of these practices to regional realities and ensure more consistent implementation. In conclusion, while continuing education is essential for the professional development of English teachers, the research underscored the need for adjustments and expansions to overcome structural barriers and maximize the positive impact on teaching practice.